1995
DOI: 10.1093/oxfordjournals.humrep.a136081
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and human conception: DNA-based X-enriched sperm separation as an adjunct to preimplantation genetic testing for the prevention of X-linked disease

Abstract: We report the world's first clinical pregnancy resulting from DNA-based enrichment for X-bearing human spermatozoa, for prevention of X-linked hydrocephalus. Sperm separation was followed by embryo biopsy and nested multiplex polymerase chain reaction (PCR) for gender determination. Enriched populations of X-bearing spermatozoa ranging from 80 to 89% pure as determined by fluorescence in-situ hybridization (FISH) resulted in in-vitro fertilization (IVF) rates indistinguishable from normal IVF procedures (65%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Even with newer approaches to detecting sex chromosome sequences (e.g. [29][30][31][32]) similar problems of misdiagnosis remained.…”
Section: Technical Issues Associated With Pgd/pgsmentioning
confidence: 99%
“…Even with newer approaches to detecting sex chromosome sequences (e.g. [29][30][31][32]) similar problems of misdiagnosis remained.…”
Section: Technical Issues Associated With Pgd/pgsmentioning
confidence: 99%
“…As described in the current report, MicroSort has been successfully employed in association with intrauterine insemination (IUI) and in vitro fertilization (IVF) with intracytoplasmic sperm injection (ICSI) to achieve numerous pregnancies, currently totaling over 1,300 live-born babies. Levinson et al [ 10 ] reported the first human pregnancy resulting from MicroSort. Fugger et al [ 11 ] reported the births of babies resulting from the use of sorted human sperm for IUI, IVF, or ICSI.…”
Section: Introductionmentioning
confidence: 99%
“…Technology today has progressed to the stage where gender selection has already become a reality for people. The world's first clinical pregnancy from sorted sperm was reported (Levinson et al 1995) some two decades ago, and 22 out of 25 embryos were analysed to be female. The concept of sorting sperm based on DNA is as follows: Sperm is stained with Hoechst 33342, and during the flow cytometry process, X-sperm (which has more DNA contents than the Y-sperm) shines more brightly when passed through the laser.…”
Section: Sorting By Sperm's Chromosomesmentioning
confidence: 99%